Dynamic changes in intramedullary pressure 72 hours after spinal cord injury - Xin Zhang; Chang-Bin Liu; De-Gang Yang; Chuan Qin; Xue-Chao Dong; Da-Peng Li; Chao Zhang; Yun Guo; Liang-Jie Du; Feng Gao; Ming-Liang Yang; Jian-Jun Li (Neural Regeneration Research, 2019)
Intramedullary pressure increases after spinal cord injury, and this can be an important factor for secondary spinal cord injury. Until now there have been no studies of the dynamic changes of intramedullary pressure after spinal cord injury. In this study, telemetry systems were used to observe changes in intramedullary pressure in the 72 hours following spinal cord injury to explore its pathological mechanisms. Spinal cord injury was induced using an aneurysm clip at T10 of the spinal cord of 30 Japanese white rabbits, while another 32 animals were only subjected to laminectomy. The feasibility of this measurement was assessed. Intramedullary pressure was monitored in anesthetized and conscious animals. The dynamic changes of intramedullary pressure after spinal cord injury were divided into three stages: stage I (steep rise) 1–7 hours, stage II (steady rise) 8–38 hours, and stage III (descending) 39–72 hours. Blood-spinal barrier permeability, edema, hemorrhage, and histological results in the 72 hours following spinal cord injury were evaluated according to intramedullary pressure changes. We found that spinal cord hemorrhage was most severe at 1 hour post-spinal cord injury and then gradually decreased; albumin and aquaporin 4 immunoreactivities first increased and then decreased, peaking at 38 hours. These results confirm that severe bleeding in spinal cord tissue is the main cause of the sharp increase in intramedullary pressure in early spinal cord injury. Spinal cord edema and blood-spinal barrier destruction are important factors influencing intramedullary pressure in stages II and III of spinal cord injury.